The Impact of Debt Financing on Financial Performance: Evidence from Retail Firms Listed on Jse: Array - Mamaro, Lenny Phulong; Legotlo, Tsholofelo Gladys (The Journal of Accounting and Management, 2020)
The study investigates the debt financing on financial performance, focusing on Retail firms listed on the Johannesburg Stock Exchange for a period of ten 10 years from 2010 to 2019. The fixed effects (FE), random effects (RE), pooled effect and the Generalized Least Square (GLS) panel data regression analysis models was applied using the financial performance ratios, Return on Equity (ROE) is used as the profitability measure and is the dependent variable, whereas; lagged ROE (LROE), Long Term Debt to Total Asset (LTDA), Total Debt to Total Asset (TDA) are used as independent variables, while Size, Sales Growth are used as control variables. The study found that LROE, TDA and GRS strongly influence financial performance (ROE) with high statistically significant of 1% level where as LTDA and SZ negatively influence financial performance with a statistically significant of 1% and 5% respectively. The study will assist retail firms to make a good decision when financing their assets to increase profit. The study contributes to literature and inform all stakeholders in the retail sector to make a profitable form of financing.